FKBP12.6 overexpression does not protect against remodelling after myocardial infarction. Issue 1 (18th July 2012) - Bito, Virginie; Biesmans, Liesbeth; Gellen, Barnabas; Antoons, Gudrun; Macquaide, Niall; Rouet‐Benzineb, Patricia; Pezet, Mylène; Mercadier, Jean‐Jacques; Sipido, Karin R.
<x xml:space="preserve">Abstract</x> Reducing the open probability of the ryanodine receptor (RyR) has been proposed to have beneficial effects in heart failure. We investigated whether conditional FKBP12.6 overexpression at the time of myocardial infarction (MI) could improve cardiac remodelling and cell Ca2+ handling. Wild‐type (WT) mice and mice overexpressing FKBP12.6 (Tg) were studied on average 7.5 ± 0.2 weeks after MI and compared with sham‐operated mice for in vivo, myocyte function and remodelling. At baseline, unloaded cell shortening in Tg was not different from WT. The [Ca2+]i transient amplitude was similar, but sarcoplasmic reticulum (SR) Ca2+ content was larger in Tg, suggesting reduced fractional release. Spontaneous spark frequency was similar despite the increased SR Ca2+ content, consistent with a reduced RyR channel open probability in Tg. After MI, left ventricular dilatation and myocyte hypertrophy were present in both groups, but more pronounced in Tg. Cell shortening amplitude was unchanged with MI in WT, but increased with MI in Tg. The amplitude of the [Ca2+]i transient was not affected by MI in either genotype, but time to peak was increased; this was most pronounced in Tg. The SR Ca2+ content and Na+— Ca2+ exchanger function were not affected by MI. Spontaneous spark frequency was increased significantly after MI in Tg, and larger than in WT (at 4 Hz, 2.6 ± 0.4 sparks (100 μm)−1 s−1 in Tg MI versus 1.6 ± 0.2 sparks (100 μm)−1 s−1 in WT MI; P < 0.05). We conclude that FKPB12.6 overexpression can effectively reduce RyR open probability with maintained cardiomyocyte contraction. However, this approach appears insufficient to prevent and reduce post‐MI remodelling, indicating that additional pathways may need to be targeted.